Optical properties of folic acid in phosphate buffer solutions: the influence of pH and UV irradiation on the UV-VIS absorption spectra and photoluminescence - Baibarac, Mihaela (Sci Rep, 2019)
Using UV-VIS absorption spectroscopy, photoluminescence (PL) and photoluminescence excitation (PLE), the photodegradation reactions of folic acid (FA) in phosphate buffer (PB) solutions were studied. Regardless of the PB solution’s pH, the UV-VIS spectra showed a gradual decrease in absorbance at 284 nm simultaneous with an increase in the absorbance of another band in the spectral range of 320–380 nm, which was downshifted under UV irradiation. The relative intensity of the FA PL band, situated in the spectral range 375–600 nm, was dependent on the pH of the PB solution. The FA PL intensity increased as increasing UV irradiation time up to 281 min. in PB solutions with pH values of 6.4 and 5.4. Under an emission wavelength of 500 nm, the position of the FA PLE spectrum changed as the PB solution pH varied from 7 to 5.4 and the irradiation time increased to 317 min. These changes were correlated with the formation of two photodegradation products, namely, pterine-6-carboxylic acid and p-amino-benzoyl-L-glutamic acid. According to UV-VIS spectroscopy and PL and PLE studies, the presence of various excipients in commercial pharmaceutical tablets does not affect the photodegradation of FA in PB solutions. Using IR spectroscopy, new evidences for the formation of the two photodegradation products of FA in PB solutions are shown.